Metode Pembelajaran Ramah Remaja di GMIT Jemaat Kalvari Maumere - Djami Bale, Sara Utami; Hattu, Justitia Vox Dei (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
Learning methods for teenagers in the church are often equated with learning methods for children. If it is differentiated, it is a kind of modification of the teaching model of children. The teachers are not treating teenagers according to their abilities and needs. Based on the context of the teenagers at GMIT Kalvari, Maumere, this research wants to reveal the extent to which the learning methods used so far are friendly or unfriendly to the teenager group of Generation Z. The research method used is qualitative research using structured interviews to the groups of teacher and teenager and review on the teaching material document